Material Processuality: Alternative Grounds for Design Research. (3rd May 2020) - Tonuk, Damla; Fisher, Tom
Abstract: This article opens discussion on the positivist epistemology underlying the understandings of materials in design research that have been brought along as a result of theory and methods inherited from engineering and psychology. Examining the ambitions of work that seeks to operationalize knowledge created by these methods in the design process, we propose that attending to the processuality of material forms is a more adequate way for design research to capture the multiplicity of materials. We develop this view by exploring the implications of the positivistic perspective that underlies recent work on new and smart materials, showing that it limits their theory and methods. This work, therefore, cannot grapple with the liveliness and fluidity of emergent cultural and material forms, and so cannot address the potential and future of emergent materialities. We conclude by arguing for the development of qualitative and ethnographic research methods that are better suited to exploring material processuality.